Um Modelo Markoviano para An??lise de Desempenho de Redes Multi-Hop Full Duplex com Interfer??ncia - Baltazar, Georgino da Silva (2023)
Fifth generation (5G) wireless communication networks have already been deployed in many parts of the world aiming to provide high data rates for the eMBB (Enhanced Mobile Broadband) scenario, a massive number of devices for the mMTC (Massive Machine Type Communication) scenario, and greatly reduced delays with very high reliability for the URLLC (Ultra Reliable Low Latency Communication) scenario. However, a number of new applications are being envisioned, integrating the physical, digital and biological worlds, whose performance requirements go beyond what can be achieved with 5G networks, demanding that a new generation begins to be researched and developed. Since the first generation of mobile communications networks, this process of evolution has taken place approximately every ten years. That is, more or less every ten years a new generation of mobile communications networks appears, which projects the start of deployment of 6G networks for the year 2030. Among the promising techniques for 6G is full duplex communication, the subject of this dissertation, which is a technology that allows a device to transmit and receive on the same physical medium at the same time. In this dissertation, we proposed an analytical Markovian model to analyze the performance of full duplex and half duplex technology combined with omnidirectional antennas and directional antennas in a multi-hop wireless network with one-way traffic taking interference into account. Several performance metrics to evaluate network performance were considered: Block Probability, Capacity, Drop Probability, Throughput, and Average Number of Elements in the system. Based on the analyses obtained, we observe that in the model where there is no buffer at the network nodes and with a higher SNR, half duplex communication combined with directional antennas has the best performance in terms of capacity and throughput. However, when we introduce buffering at the network nodes, full duplex technology combined with directional antennas and with high SNR performs much better than half duplex technology. Keywords: 6G, 5G; Full Duplex communication; SNR; Performance Analysis; Markov Processes, directional antennas, omnidirectional antennas, interference